Review of the cost of venous thromboembolism - Fernandez MM; Hogue S; Preblick R; Kwong WJ (Dove Medical Press, 2015)
Maria M Fernandez,1 Susan Hogue,1 Ronald Preblick,2 Winghan Jacqueline Kwong2 1RTI-Health Solutions, Market Access and Outcomes Strategy, Research Triangle Park, NC, 2Daiichi Sankyo, Inc., Health Economics & Outcomes Research, Parsippany, NJ, USA Background: Venous thromboembolism (VTE) is the second most common medical complication and a cause of excess length of hospital stay. Its incidence and economic burden are expected to increase as the population ages. We reviewed the recent literature to provide updated cost estimates on VTE management. Methods: Literature search strategies were performed in PubMed, Embase, Cochrane Collaboration, Health Economic Evaluations Database, EconLit, and International Pharmaceutical Abstracts from 2003–2014. Additional studies were identified through searching bibliographies of related publications. Results: Eighteen studies were identified and are summarized in this review; of these, 13 reported data from the USA, four from Europe, and one from Canada. Three main cost estimations were identified: cost per VTE hospitalization or per VTE readmission; cost for VTE management, usually reported annually or during a specific period; and annual all-cause costs in patients with VTE, which included the treatment of complications and comorbidities. Cost estimates per VTE hospitalization were generally similar across the US studies, with a trend toward an increase over time. Cost per pulmonary embolism hospitalization increased from $5,198–$6,928 in 2000 to $8,764 in 2010. Readmission for recurrent VTE was generally more costly than the initial index event admission. Annual health plan payments for services related to VTE also increased from $10,804–$16,644 during the 1998–2004 period to an estimated average of $15,123 for a VTE event from 2008 to 2011. Lower costs for VTE hospitalizations and annualized all-cause costs were estimated in European countries and Canada. Conclusion: Costs for VTE treatment are considerable and increasing faster than general inflation for medical care services, with hospitalization costs being the primary cost driver. Readmissions for VTE are generally more costly than the initial VTE admission. Further studies evaluating the economic impact of new treatment options such as the non-vitamin K antagonist oral anticoagulants on VTE treatment are warranted. Keywords: deep vein thrombosis, pulmonary embolism, costs, pharmacoeconomics, resource utilization